Is Inequality in Africa Really Different? - Milanovic, Branko (World Bank, Washington, DC, 2014)
High inequality in Africa is something of a paradox: Africa should be a low-inequality continent according to the Kuznets hypothesis (because African countries are poor and agriculture-based), and also because land (the main asset) is widely shared. The author's hypothesis is that African inequality is politically determined. Yet in the empirical analysis, despite the introduction of several political variables, there is still an inequality-increasing "Africa effect" linked to ethnic fractionalization. The politics, however, may work through ethnic fractionalization, which provides an easy and secure basis for the formation of political groups. Although this is a plausible explanation, it is not fully satisfactory, and the author criticizes it in the concluding section.